Rancang Bangun Sistem Informasi Potensi dan Peluang Investasi Berbasis WebGIS - Budi Sunaryo; Joni Sukma Wardana; Reihan Hanafi Wiyanatra; Arnita Arnita; Riska Amelia; Zonna Eva Karmila (Bulletin of Computer Science Research, 2022)
Regional potential can create investment opportunities and help the economic growth of the surrounding community. Limited information, difficulty understanding data, unclear data pictures, and ineffective media make it difficult for potential investors to invest. The information picture must be easily accessible and provide a clear picture. Web Geographic Information System (WebGIS) is a web-based platform using Geographical Information System (GIS) technology. WebGIS can display information about an area's potential and investment opportunities through its distribution map. This research uses the prototype method where each stage refers to user needs. Based on the results of testing and implementation of this WebGIS-based information system design, potential information needs can be visualized through the location position and size of the area in the form of polygons on the map. Accessibility of data visualization via the internet helps potential investors to find out early about possible area information without having to come to the location first.